Method and system for real-time generation of reference navigation path for navigation of vehicle - Sunil Kumar, Balaji; Sarkar, Manas (2020)
Disclosed subject matter relates to a field of telematics that performs a method for generating reference navigation path in real-time for safe navigation of vehicle. A path generation system associated with the vehicle may receive a pre-generated navigation path, between source point and destination point. Further, the path generation system may identify a plurality of values corresponding to current condition of the vehicle, for a selected segment while the vehicle is navigating along the pre-generated navigation path. Further, an angular shift of the vehicle is determined based on the current condition of the vehicle and a reference navigation path is generated for the selected segment based on the angular shift. The present disclosure eliminates need for continuous monitoring and steering angle adjustment to align the vehicle with the pre-generated navigation path, thereby reducing power consumption by the vehicle and also minimizing jerks experienced by the vehicle.